ANALYSIS OF FACTORS CAUSING THE PRODUCT PURCHASED BY CONSUMERS BASED ON DATA ON THE SALE OF GOODS IN A MARKET PLACE IN INDONESIA - Baihaqi Siregar; Erna B Nababan; Opim S Sitompul (Talenta Publisher, 2018)
Starting from the success of giant web service companies as well as Google and Facebook in managing and utilizing unstructured data in the form of consumer generated media and click stream in a very large volume, a concept known as Big Data then became the center attention in the world of information technology. The fact also shows that more and more organizations in the world, whether private companies or government agencies, have difficulty managing data whose volumes are growing and their types are increasingly complex. They have to organize and analyze these data, and they must find the meaning or value of the ever-expanding and increasingly complex data pile, which is said to have exceeded the capability of conventional data processing applications to process it. The condition of this kind of data is also categorized as Big Data, which is interpreted as a set of data in a very large number of challenges lies in how the data should be stored, how to search in the pile of data, how to distribute it, how to visualize it, and how the data should be analyzed. The long-term goal of IbKIK's proposed program is the establishment of a startup company in the field of analytic data from the world of campus directly. Within the planned three-year period, it is desirable that the company be financially self-sufficient by being a data analytics consultant and also creating a sophisticated and advanced Big Data Analytic application platform product. The advantages possessed when the company started from the academic world is the quantity and quality of human resources as intellectual actors can be selected quickly and accurately. Especially with the synchronization between the curriculum content that is taught with its implementation directly through the program IbKIK become useful products and economic value. From the academic point of view, the desired outcomes are from this program published several journals and proceedings of national and international scale, the publication of textbooks, getting HKI, and publications in the mass media. Also, with the success of this company can produce a derivative company engaged in other areas that are still related as a supporter of the business. The product output of the community service activity that has been done for the first year of the planned three years period is the establishment of a Product Information System Sold on E-Commerce Transactions at Market Place. Also, has been established research unit as the forerunner of the business unit under the auspices of the Faculty of Computer Science and Information Technology University of Sumatera Utara under the name Data Science Research Group.